The history of the mining industry in Mberengwa 1890-2014 - Gumbo, Nyashadzashe (Midlands State University, 2017)
The study wishes to explore the history of the mining industry in Zimbabwe from the period of its establishment prior to 2014. It looks at the changes brought to the Mberengwa communities by the establishment of the mining companies. Mining evicted local communities and were robbed their ancestral land. It affected agriculture in many ways in the mining communities. The study also explores the subsequent fall of the multinational mining companies in Mberengwa that left local people exposed to poverty and unemployed. Closure of the multinational companies led to the rise and establishment of small scale mining in Mberengwa. It also looks at the impact of the mining industry since 1980 in Mberengwa. Mining was affected by the liberation war so after1980 there was now black empowerment. Mining as a whole had both positive and negative connotations to the communities. The Mberengwa authorities in particular and the government in general have put various measures in order to boost development through the mining sector. Mberengwa communities also have campaigned for proper mining that can bring development as the district is lagging behind when it comes to development. Archival sources and reports were used to come out with this detailed research. Some Interviews with former mine workers, old people, chiefs, schools, mine workers and police officers were carried out to come with this project.